Analytical study of the mapping of brazilian companies committed to the UN 2030 agenda - Ferrari, Maria Aparecida; Cabral, Raquel [UNESP]; Salhani, Jorge [UNESP] (Univ Comunitaria Regional Chapeco-unochapeco, 2022)
Purpose: the purpose of this paper is to analyze the profile and the trends of the Brazilian organizations committed to the 2030 Agenda through the mapping of the Brazilian signatories to the United Nations Global Compact (Network Brazil). Method/approach: a bibliographic survey was used to assemble a theoretical framework on the UN Global Compact and its correlations with the organizations. We also conducted a descriptive analysis of the Brazilian organizations that are signatories to the Compact. Main findings: until June 2019, 838 organizations were signatories to the Compact in Brazil: 13,4% belonged to the public sector, 62,3% to the private sector, and 24% to the non-profit, non-governmental sector. We observed that the main signatories in Brazil are large enterprises and non-governmental organizations. Methodological/social/managerial contributions: the main contributions of this article have to do with its theoretical framework and the mapping of the organizations, which allowed the identification of trends and positions of the Brazilian signatories in relation to the 2030 Agenda and the SDGs. We consider the organizations as agents that create social discourses, and with their corporate persona may influence the public opinion. Originality/relevance: the originality of this study lies on, in addition to mapping all Brazilian companies and organizations that are signatories to the Global Compact, the attempt to identify the particularities of the Brazilian context in relation to the implementation of the 2030 Agenda and the Sustainable Development Goals.
Keywords: 2030 Agenda; Sustainable Development Goals; United Nations Global Compact